Startups in Action - Silva, JP (Ascent Audio, 2020)
The growing pains of a startup's initial year in business require a keen awareness of uncertainties and a willingness to adapt in order to survive. Today's new founders greatly benefit from taking a behind-the-scenes look at successful companies such as Etsy, HotelTonight, Fiverr, and more in regards to how they overcame the challenges of their first year. Startups in Action is your curated source for critical insights and inspiration from those who have been there before. This book documents the month-to-month journeys of these companies in their first year, zeroing in on key decisions that helped them recover from missteps, and adapt to complications, to eventually grow and succeed. Were the founders full-time from the beginning? How long did it take them to build a working prototype? How many end-users did they have in the first year? The answers to these questions are of interest to those who are just starting out and want to learn by example. Collected from interviews with the founders themselves, author JP Silva answers these questions and reveals how each of the startups charted their paths to success. Startups in Action is equal parts inspirational and practical, providing guidance through a foundation of relatability to help cope with situations and surprises experienced during a startup's first year.